Implementasi Nilai Profetik dalam Membentuk Karakter Siswa di Madrasah - Muhammad, Muhammad; Syihabuddin, Muhammad Arif (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
The importance of the implementation of prophetic values in the formation of student character in madrasas, especially in MTs Al-Hafizh Surabaya. Emphasis on affective and psychomotor aspects in education is urgently needed to overcome various deviant behaviors among students, such as brawls and drug abuse. Prophetic education, which is grounded in the values of humanization, liberation, and transcendence, offers an approach to developing students' potential and strengthening their faith. This study uses a qualitative type of research. Data and documents were collected and compiled using in-depth interview techniques, participant observation and documentation studies. The data and documents are then checked for validity through triangulation of sources, techniques and time. Furthermore, the data and documents are analyzed in a qualitative descriptive manner. The result of this research is that MTs Al-Hafizh has implemented prophetic values into the school's vision and mission, through routine activities such as congregational prayers and religious learning. The active role of principals, teachers, and homeroom teachers in internalizing these values is very important, supported by intense communication with students' parents. Thus, it is hoped that students can develop good character, integrity, and responsibility, be ready to face the challenges of the times and contribute positively to society.